2023
DOI: 10.1021/acsami.3c05159
|View full text |Cite
|
Sign up to set email alerts
|

How Matrixes Influence Room Temperature Ultralong Organic Phosphorescence: 4-Dimethylaminopyridine vs Carbazole Derivative

Abstract: How matrixes influence room temperature ultralong organic phosphorescence (RTUOP) in the doping systems is a fundamental question. In this study, we construct guest-matrix doping phosphorescence systems by using the derivatives (ISO2N-2, ISO2BCz-1, and ISO2BCz-2) of three phosphorescence units (N-2, BCz-1, and BCz-2) and two matrixes (ISO2Cz and DMAP) and systematically investigate their RTUOP properties. Firstly, the intrinsic phosphorescence properties of three guest molecules were studied in solution, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…It is revealed that the ultralong phosphorescence in the powder matrix is from charge separation and charge recombination according to transient absorption. Then, we found that 7 H -benzo­[ c ]­carbazole (BCz), , 5 H -benzo­[ c ]­carbazole (BCz-1), , N -phenyl-1-naphthylamine (N-1), and N -phenyl-2-naphthylamine (N-2) function similarly with Bd in terms of UORTP. Due to the similar phosphorescence properties of these five organic units, we defined them as “ Phosphorescence Unit ”.…”
Section: Introductionmentioning
confidence: 99%
“…It is revealed that the ultralong phosphorescence in the powder matrix is from charge separation and charge recombination according to transient absorption. Then, we found that 7 H -benzo­[ c ]­carbazole (BCz), , 5 H -benzo­[ c ]­carbazole (BCz-1), , N -phenyl-1-naphthylamine (N-1), and N -phenyl-2-naphthylamine (N-2) function similarly with Bd in terms of UORTP. Due to the similar phosphorescence properties of these five organic units, we defined them as “ Phosphorescence Unit ”.…”
Section: Introductionmentioning
confidence: 99%
“…As the host PXT molecule has low melting point (52 o C), therefore, the radicals are would be quenched due to their enhanced thermal motion. 40,62 This indicates that the irradiated doped material can recover to its original state after melting-recrystallizing procedure. By heating and recrystallization, the color of the powder changed to original white (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…33,[35][36][37][38] The long lifetime of the excited state provides much more opportunities to photo-induced charge separation between the host and guest. 33,39,40 After the charge separation, the stabilization of the unpaired electrons may offer a new strategy to construct the stable organic radicals. 18,41,42 In addition, a rigid host restricts the molecular motions, thus decreasing the non-radiative decay for the realization of emissive radicals.…”
Section: Introductionmentioning
confidence: 99%
“…PMMA and PVA are frequently used as polymer hosts as they can provide a rigid environment to significantly inhibit nonirradiative relaxation of triplet excitons. Compared with the host, the guest library expands more discretely. Till date, derivatives of 1 H -benzo­[f]­indole (Bd), , 7 H -Benzo­[c]­carbazole (BCz), 5 H -Benzo­[c]­carbazole (BCz-1), , N -phenyl-1-naphthylamine ( N -1), N -phenyl-2-naphthylamine ( N -2), phenylboronic acid, and so forth have been reported as excellent guests. It is worth mentioning that some guests (such as Bd, BCz, BCz-1, etc.)…”
Section: Introductionmentioning
confidence: 99%